ANALISIS PENGARUH RISK ASESSMENT (PENILAIAN RESIKO) TERHADAP KECELAKAAN TAMBANG PADA KEGIATAN PENAMBANGAN BATUBARA (STUDI KASUS DI PT. BATURONA ADIMULYA) - KM Ade Isnaini; zulfkifli Dahlan; syamsul komar (Jurnal Teknik Patra Akademika, 2017)
PT. Baturona Adimulya refers to PKP2B which is engaged in coal mining. PT. Baturona Adimulya has begun its coal mining activities since 2010. According to the research conducted from 2010 until 2016, there were one mining accident with severe injuries, two adverse events and eleven accidents causing property damages. The frequency level of the mining accident at PT. Baturona adimulya was approximately at level 3(possible) which means mining accidents can occur anytime with the level of incidents probability 26% until 50.99%, and the severity rate was approximately at 2 (minor) which means mining accidents that occur only cause minor injury. Based on the value plotting of the severity and frequency rate at Risk Assessment Matrix, the value of 6 (six) in the green zone was obtained which means the risk is low or minor as it can still be acceptable, additional control is not neceessary, but review on the potential hazard still needs to be done to prevent further risks. Risk Assessment in the form of JSA and SOP have been owned by PT. Baturona adimulya since 2011. There were 79% of 14 mining accidents happened in the period of 2010 until 2016 when JSA and SOP have already existed. The cause accidents persisted was 89.1% human error, 10.9% environment, and management which did not seem to have influence, but in fact it had big influence based on the review of the domino effect theory of heinrich. The efforts which can be done for the prevention of mining accidents are legislation, fixed standards, supervision, researchs which tend to be engineering, medical research, psychological and statistics, education and training, encouragement, insurance, company management commitment